Peran Regulasi Diri dan Konformitas terhadap Perilaku Berkendara Berisiko pada Remaja - Happy Virgina Puspa Nirmala; Bhina Patria (Faculty of Psychology, Universitas Gadjah Mada, 2016)
There are a number factors that contribute to the traffic accident at adolescents. One of them is the implementation of risky driving behaviour. The psychological factros that can be the predictors of risky driving behaviour are self-regulation and conformity. The aim of this research is to identify the factors’ role of risky driving behaviour at young novice drivers. The study involved adolescents aged 16 to 18 who were eligible subjects of the study. This study uses an adaptation of the Driving Behaviour Quetionnaire (DBQ) and The Czech Self-Regulation Quetionnaire (SRQ-Cz). Hypotheses of this research is that self-regulation and conformity have contribution to the risky driving behaviour. Regression analysis shows that self-regulation and conformity 13.5% contribute to the risky driving behaviour simultaneously, 6.5% is from self-regulation and 7% from conformity (F= 6,29; p<0,05). Analysis also shows that self-regulation has negative correlation to the risky driving behaviour where as conformity has positive correlation to the risky driving behaviour.